2014
DOI: 10.1080/01904167.2014.957390
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Straw and Manure on Crop Micronutrient Nutrition under a Wheat-Maize Cropping System

Abstract: 2 Management practices have significant effects on crop micronutrient contents. This study examined effects of applying chemical fertilizers of nitrogen (N), phosphorus (P), and potassium (K) (NPK), alone or supplemented with straw or manure, under a wheat-maize cropping system in a 18-year experiment, on the crops' iron (Fe), manganese (Mn), copper (Cu), and zinc (Zn) contents throughout the crops' development. The micronutrient contents of both wheat and maize were above critical values during vegetative dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…According to Campbell [ 37 ], the critical concentration of Fe in wheat plants during the vegetative phase is 25 mg kg –1 , and the sufficiency concentration range for Fe in wheat flag leaves during the grain-filling stage is 30–200 mg kg –1 . In the present study, the Fe concentrations in the wheat straw during the maturity stage ranged from 210 to 406 mg kg –1 ( Table 6 ), which were similar to those found by Li et al [ 18 ] and Zhang et al [ 38 ]. Thus, our results and those of other studies indicate that organic fertilizer enhanced the concentration of Zn in wheat but decreased the concentration of Mn compared with the use of a chemical fertilizer [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to Campbell [ 37 ], the critical concentration of Fe in wheat plants during the vegetative phase is 25 mg kg –1 , and the sufficiency concentration range for Fe in wheat flag leaves during the grain-filling stage is 30–200 mg kg –1 . In the present study, the Fe concentrations in the wheat straw during the maturity stage ranged from 210 to 406 mg kg –1 ( Table 6 ), which were similar to those found by Li et al [ 18 ] and Zhang et al [ 38 ]. Thus, our results and those of other studies indicate that organic fertilizer enhanced the concentration of Zn in wheat but decreased the concentration of Mn compared with the use of a chemical fertilizer [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…Li et al [ 47 ] reported a positive balance of the macronutrients in the soil under manure treatment in the central northern region of China. Zhang et al [ 38 ] reported that the application of NPK alone resulted in micronutrient deficits, but not when the application of NPK was supplemented with manure. In the present study, the balance calculations for heavy metals showed that the application of compost increased the soil levels of Pb, Cd, and Cr ( Table 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, applying a combination of organic and chemical fertilizers increases the content of middle- and micro-nutrients in soil and plant, promoting absorption of nutrients by crops and increasing grain yield. In contrast, applying chemical fertilizers alone showed the opposite effect (Zhang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The content of middle- and micro-nutrients affect maize growth and development and the nutritional quality of the grain, which are closely associated with human health (Zhang et al, 2015 ; Wajid et al, 2020 ). This study found that both middle- and micro-nutrients in soil and grain showed a significant positive correlation with the OFSR and soil C fractions ( Figures 4A , B ), indicating that OFS treatments increased C fractions content and increased the content of some middle- and micro-nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Dhaliwal et al, (2011) reported distribution of total micronutrient fractions and their contribution towards availability and plant uptake of micronutrient under long term maize-wheat cropping sequence indicated residual micronutrients as the dominant proportion of total Zn and Cu. Zhang et al, (2008) observed the long term effect of manure application on micronutrients availability under rice-wheat and maize-wheat cropping systems. They reported that the DTPAextractable Zn and Cu availability was higher in maize-wheat cropping system as compared to rice-wheat cropping system.…”
Section: Introductionmentioning
confidence: 99%